Les émotions dans la formation enseignante : une perspective historique - Catherine Audrin (Recherches en Éducation)
Throughout their lives, individuals act and think according to their cognitive experiences, but also according to past and present emotional experiences. While research has shown the importance of emotions on memorization (Montagrin, 2013), attention (Brosch, Sander, & Scherer, (2007) and decision-making (Auteur and Sander, 2018), this paper focuses on the importance of emotions in learning, listing research conducted in a school context or more broadly in an academic context. This article provides a synthesis of the literature on the issue of emotions and their relationship to learning. By adopting a historical perspective, it aims to present the context in which emotions have emerged as an important element in learning and became an integral part of it today. Literature suggests that studying learning requires a broad perspective including not only the cognitive dimension of learning, but also the place of emotions in this process (Capron Puozzo, 2013). Thus, we propose avenues of reflection for the integration of the emotional dimension and the sensitization of future teachers to this aspect.